Pengaruh Kepemimpinan Transformasional terhadap Perilaku Kerja Inovatif: Peran Motivasi untuk Belajar dan Budaya Organisasi Ambidextrous: THE EFFECT OF TRANSFORMATIONAL LEADERSHIP ON INNOVATIVE WORK BEHAVIOR: THE ROLE OF MOTIVATION TO LEARN AND AMBIDEXTROUS ORGANIZATIONAL CULTURE - Hertina, Dewi Ariani; Etikariena, Arum (Puslatbang KHAN, 2024)
Indonesia is ranked 61st out of 132 countries in the world based on innovation capability. This shows that Indonesia needs to strive so that can improve innovation capabilities, from the organizational level to the individual level. This research was conducted to examine the moderating role of ambidextrous organizational culture on the direct effect of transformational leadership on innovative work behavior as well as the indirect effect through motivation to learn. This research was conducted on ASN through a survey distributed online using a self-report questionnaire. Data were analyzed using Hayes’ PROCESS models 4 and 15 with SPSS version 26 software. The results show that motivation to learn fully mediates the effect of transformational leadership on innovative work behavior. In addition, ambidextrous organizational culture does not moderate either the direct or indirect effect of transformational leadership on innovative work behavior. This shows that transformational leadership requires the mediating role of motivation to learn so that innovative work behavior can occur. However, it turns out that an ambidextrous organizational culture cannot strengthen employees’ innovative work behavior. This research provides a foundation for organizations to encourage motivation to learn through the application of transformational leadership, which can then have an impact on employee innovative behavior